Microwave-Assisted Copper-Catalyzed Cross-Coupling Reaction of Alkynes with Aryl Iodides and Vinyl Halides - Tsai, Wen-Ting; Lin, Yun-Yung; Wang, Yu-Jen; Lee, Chin-Fa (Synthesis, 2012)
The microwave-assisted, copper-catalyzed coupling of terminal alkynes with aryl iodides and vinyl halides is reported. In general, the reactions are completed in 10–30 min using 2–5 mol% [CuI(xantphos)] as a catalyst to provide the corresponding alkynes and enynes in good to excellent yields. A broad spectrum of aryl iodides, vinyl iodides, and bromides are coupled with aryl- and alkyl alkynes.
Keywords: microwaves; copper; cross-coupling; alkynes; aryl iodide